Impedance spectroscopy of lead-free (1-x-y)Bi0.5Na0.5TiO3–xBi0.5K0.5TiO3–yBi0.5Li0.5TiO3 piezoelectric ceramics. Issue 177 (2nd January 2017) - Bongkarn, Theerachai; Cann, David P.; Prasertpalichat, Sasiporn; Kumar, Nitish; Sumang, Rattiphorn
ABSTRACT: The AC complex impedance spectroscopy technique has been used to characterize electrical parameters of polycrystalline sample of (1- x-y )Bi0.5 Na0.5 TiO3 – x Bi0.5 K0.5 TiO3 – y Bi0.5 Li0.5 TiO3 (0.90- x BNT- x BKT-0.10BLT and 0.80- y BNT-0.20BKT- y BLT) lead-free ferroelectric ceramics with 0.18 ≤ x ≤ 0.26 and 0 ≤ y ≤ 0.12 in a wide frequency range at different temperatures. These samples were prepared by combustion technique. The crushing sintered pellets exhibited pseudocubic symmetry in all the samples. Impedance measurement on 0.90- x BNT- x BKT-0.10BLT and 0.80- y BNT-0.20BKT- y BLT in the temperature range of 470–560°C as a function of frequency has been analyzed. The bulk resistivity of ceramics decrease with increase temperature similar to semiconductor, and the Cole-Cole (Nyquist) plot presented negative temperature coefficient of resistance (NTCR). The activation energies of bulk and grain boundary for composition addition of BKT( x ) and BLT (y) ceramics were found to be ∼ 0.5–0.7 eV, which suggested a conduction mechanisms dominated by extrinsic defects.